2009
DOI: 10.1088/1748-9326/4/4/045015
|View full text |Cite
|
Sign up to set email alerts
|

Record Russian river discharge in 2007 and the limits of analysis

Abstract: The Arctic water cycle has experienced an unprecedented degree of change which may have planetary-scale impacts. The year 2007 in particular not only was unique in terms of minimum sea ice extent in the Arctic Ocean but also was a record breaking year for Eurasian river inflow to the Arctic Ocean. Over the observational period from 1936 to 2006, the mean annual river discharge for the six largest Russian rivers was 1796 km 3 y −1 , with the previous record high being 2080 km 3 y −1 , in 2002. The year 2007 sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 27 publications
11
108
0
Order By: Relevance
“…Gimeno et al [49] have previously demonstrated the relation between intensification of this moisture source and increased moisture contribution over the Eurasian river basins. This finding is especially relevant because the Atlantic Ocean was previously found to be one of the most important sources for the Eurasian river basins [50]. In agreement with our result, Zhang et al [32] observed an increased moisture transport into the Eurasian river basins, and Shiklomanov and Lammers [50] described a peak river discharge in 2007.…”
Section: Discussionsupporting
confidence: 92%
“…Gimeno et al [49] have previously demonstrated the relation between intensification of this moisture source and increased moisture contribution over the Eurasian river basins. This finding is especially relevant because the Atlantic Ocean was previously found to be one of the most important sources for the Eurasian river basins [50]. In agreement with our result, Zhang et al [32] observed an increased moisture transport into the Eurasian river basins, and Shiklomanov and Lammers [50] described a peak river discharge in 2007.…”
Section: Discussionsupporting
confidence: 92%
“…A general picture of increasing runoff trends in the panArctic drainage basin has been established in recent years (Peterson et al 2002Dyurgerov and Carter 2004;McClelland et al 2006;Shiklomanov and Lammers 2009). Dyurgerov et al (2010) have further reported that river runoff to the Arctic Ocean has increased independently of, but with similar magnitude as the increase in freshwater input from glacier melting.…”
Section: Discussionmentioning
confidence: 99%
“…Local anthropogenic water-use changes, for instance the construction and use of dams, may also influence the runoff and complicate the assessment of precipitation-runoff relations (Shibuo et al 2007;Adam et al 2007;Rawlins et al 2009b;Shiklomanov and Lammers 2009), although the effect of dams on annual discharge in the Arctic is generally small over longer time periods . In the Churchill basin, however, large-scale diversions of water out of the basin have strongly influenced the river flow (Déry et al 2005), yielding a considerably greater decrease in runoff than in precipitation over the studied period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also showed increasing positive trends in both precipitation amount and air temperature (Figures 2a and 3b). According to Shiklomanov and Lammers [6], river discharge from the large Russian basins (e.g., Yenisey, Ob and Lena) into the Arctic Ocean peaked in 2007 due to the increase in precipitation across the northern parts of the basins and intensive permafrost thawing. Consequently, the economic costs associated with the implementation of flood countermeasures in 2007 reached approximately 2% of the revenue of the Sakha Republic of the Russian Federation [8].…”
Section: Recent Climate Change In Arctic Regionsmentioning
confidence: 99%